FROM NATIONAL DEFENCE DIRECTIVE TO NATIONAL MARITIME SECURITY STRATEGY: TREND TOWARDS THE INTEGRATION OF CIVIL AND MILITARY CAPABILITIES IN THE MARITIME FIELD (Journal of the Spanish Institute for Strategic Studies, 2018)
This paper aims to demonstrate that new risks and threats at sea, the phenomenon of globalisation and international commitments are just some of the factors that have driven the development of the so-called comprehensive approach to security in Spain.The search for civil-military synergy at sea is a factor that shapes security strategy and defence policy in our country. Key words: Strategy and policy; security and defence in Spain; comprehensive approach to the sea